Student plagiarism in an online world problems and solutions - Roberts, Tim S., 1955- (Hershey, PA : Information Science Reference, 2008)
'This book describes the legal and ethical issues surrounding plagiarism, the tools and techniques available to combat the spreading of this problem, and real-life situational examples to further the understanding of the scholars, practitioners, educators, and instructional designers who will find this book an invaluable resource'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references (p. 263-286) and index.
Description based on print version record.
Keywords: Plagiarism -- Prevention; Cheating (Education) -- Prevention; Internet research -- Moral and ethical aspects; Electronic books